"All real life is encounter" On the sustainable relevance to be surprised and affected. (3rd July 2019) - Schmid, Peter F.
ABSTRACT: Encounter is much more than a way of practicing psychotherapy or group work. These practices are just applications of a basic anthropological, epistemological and (socio-)ethical stance on how we humans find ourselves in the world and how we can choose to relate to other human beings, groups, communities, the society, givens in the world and the world as such. This paper tries to call to mind and revive the fundamental, provocative and thought-provoking notion of encounter as a way of being in relationship to persons, society and the world we live in. All concretizations of encounter must be critically measured by the challenge of its profound meaning.